In context to an non-inverting op-amp (from text book) Vin = Vo x Ri/Ri + Rf Rearranging: Vo = (1 + Rf/Ri) x Vin I believe Ri is the common factor from the first equation, but I dont know how to get to the second equation. If any one can give me the sequence of steps?
First, the equation you have shown should have parenthesis around the two terms in the denominator like below. Vin = Vo x Ri/(Ri + Rf) Start by multiplying both sides of the equal sign by (Ri + Rf). Next, multiply both sides of the equal sign by Ri. Then, you should have the expression Vo = Vin*(Ri+Rf)/Ri Next, expand the fraction to Vin*(Ri/Ri + RF/Ri) Since Ri/Ri = 1 then you can substitute to get: Vo = Vin*(1+(Rf/Ri))